Isolation and identification of Clostridium chauvoei from cattle in Mymensingh city of Bangladesh - Alam, Md Nur; Mahmud, Md Muket; Nime, Jannatun; Khan, Md Roknuzzaman; Khan, Md. Shahidur Rahman; Rahman, Md Bahanur; Nazir, K H M Nazmul Hussain (Fundamental and Applied Agriculture, 2018)
Black quarter (BQ), caused by Clostridium chauvoei, is an economically im- portant, highly infectious bacterial disease of cattle, goat and sheep. The present study was conducted to isolate and identify the causal agent of BQ from field cases. A total of 32 samples from necropsied areas of suspected cattle brought to the Veterinary Teaching Hospital, Bangladesh Agricultural University, Mymensingh were collected. The samples were subjected for bacteriological culture followed by identification through a series of conven- tional bacteriological techniques, staining properties and biochemical tests. The bacteria were cultured in anaerobic condition using candle jar. Morpho- logical characters of bacteria were observed after Gram stain. The suspected samples were subjected for several passages in liver infusion broth to get pure culture. On neomycin blood agar, the bacteria showed hemolysis. Based on the cultural and staining characteristics and biochemical tests, 4 (12.5%) out of 32 samples were detected as Clostridium chauvoei. It is concluded that Cl. chauvoei has been successfully isolated and identified from BQ affected cattle.